Policing Proof-of-Stake Networks: Regulatory Challenges Presented by Staking-as-a-Service Providers and the Need for a Tailored Regime - Hart, Jessica (Science and Technology Law Review, 2022)
Blockchain networks have increasingly turned to proof-of-stake (“PoS”) protocols as a mechanism for discouraging bad behavior and securing participants’ data. In doing so, they have not only improved their energy consumption but also increased their accessibility. Still, the technological proficiency required of participants in PoS networks presents certain barriers to inclusivity. Third-party services known as staking-as-a-service (“StaaS”) providers have emerged as a popular solution to participants personally securing the network. The nature of this sub-contractual relationship has raised questions regarding the need for their regulation. In response to regulatory concerns, some practitioners have suggested that StaaS arrangements should qualify as “investment contracts” per SEC v. Howey and thus “securities” under the Securities Act of 1933. While much litigation has surrounded the question of whether cryptocurrencies vis-à-vis initial coin offerings (“ICOs”) constitute securities, none has yet addressed the question on StaaS providers within these networks. Accordingly, this Note explores the potential arguments in favor and against regulating StaaS providers as issuers of securities under Howey. It argues that the uniqueness of and variations among StaaS contracts make these arrangements unsuitable for regulation as securities. Instead, both StaaS users and PoS networks at large can benefit from a regulatory framework tailored to this innovative and nuanced technology.